Clinical Outcomes of Acute Achilles Tendon Rupture Repair Utilizing Supine Positioning. Issue 4 (16th October 2019) - Rogero, Ryan; Beck, David; Larwa, Joseph; Fuchs, Daniel; Raikin, Steven M.
Category: Sports, Trauma Introduction/Purpose: With no consensus regarding the optimal technique for repair of Achilles tendon ruptures, identifying techniques which minimize complications and maximize functional outcomes is essential. Previous studies on Achilles repair performed in the supine position have demonstrated low complication rates, avoidance of issues related to anesthesia set-up of prone positioning, and decreased operating room times, though these studies have included relatively low patient numbers and lacked functional outcomes. The purpose of this study is to evaluate the clinical outcomes of a large cohort of patients undergoing acute Achilles tendon repair in the supine position. Methods: We conducted a retrospective review of patients undergoing open repair of acute Achilles tendon ruptures with supine positioning by one fellowship-trained foot & ankle surgeon at a single outpatient surgical location from 2010-2016. During each procedure, a longitudinal incision was made just medial to the tendon extending approximately 3.5 cm both proximally and distally from the level of the rupture. Exclusion criteria included age <18 years old, repair >21 days from date of injury, and undergoing any additional procedures other than concomitant tendon transfers. Postoperative chart notes were reviewed to identify any complications experienced by patients, and surgical site records were reviewed for tourniquet times. Patients were contacted and asked about their satisfaction with surgical outcome and to complete the Foot & Ankle Ability Measure (FAAM)- Activities of Daily Living (ADL) and –Sports subscales, as well as the Visual Analog Scale (VAS) for pain. Results: Two-hundred eleven patients, including 31 (14.7%) females, were included in the study, with a mean age of 40.9 years and mean BMI of 28.8 kg/m2. Patients had an average of duration from injury to surgery of 8.5 days (range, 1-21 days) and mean tourniquet time of 35.5 minutes (range, 16-77 minutes). Four patients (1.9%) experienced a postoperative complication, including 2 superficial wound infections and 2 deep vein thromboses. There were no sural nerve-related injuries or tendon re-ruptures. At an average of 56.8 months postoperatively (range 24-99 months), patients reported a mean VAS pain of 0.6 ± 1.3/10 and mean FAAM-ADL and FAAM-Sports scores of 93.9 ± 12.4/100 and 84.7 ± 19.6/100, respectively. Additionally, 91.4% reported being satisfied with the outcome of the surgery. Conclusion: With an extremely low complication rate, mid- to long-term functional scores comparable to other reported Achilles tendon repair techniques, and high rate of patient satisfaction, open repair of Achilles tendon ruptures performed in a supine position offers surgeons a safe and effective treatment method.